The new IASLC grading system for invasive non‐mucinous lung adenocarcinoma is a more useful indicator of patient survival compared with previous grading systems. Issue 1 (13th September 2022) - Yanagawa, Naoki; Sugai, Mayu; Shikanai, Shunsuke; Sugimoto, Ryo; Osakabe, Mitsumasa; Uesugi, Noriyuki; Saito, Hajime; Maemondo, Makoto; Sugai, Tamotsu
Abstract: Background: The International Association for the Study of Lung Cancer (IASLC) Pathology Committee recently proposed a new histological grading system for invasive lung adenocarcinoma (ADC). This study evaluated the usefulness of this grading system. Methods: A total of 395 patients with ADC were examined. ADCs were reclassified based on comprehensive histological subtyping according to the IASLC grading system. We evaluated the following histological grading systems for invasive ADC: the architectural (Arch), Sica's grading, and IASLC grading systems. Multivariate analyses of overall and recurrence‐free survival (RFS) based on these three grading systems were performed using Cox proportional hazards models. Results: Multivariate analysis showed that all three grading systems were useful for predicting the outcomes of patients at all stages. However, the IASLC grading system was superior to the Arch and Sica's grading systems in differentiating grade 3 from grade 1 ADCs in terms of both overall survivals (IASLC vs. Arch vs. Sica's grading systems: hazard ratio [HR] = 3.77 vs. 3.03 vs. 2.63) and RFS (HR = 4.25 vs. 2.69 vs. 2.4). Conclusion: The newly proposed IASLC grading system was useful for predicting patient outcomes and was superior to the other grading systems in detecting high‐grade malignancy.